TREM1 AS AN IMPORTANT PARTICIPANT IN THE DEVELOPMENT OF CRITICAL COMPLICATIONS IN HEART SURGERY PATIENTS - Maria Vladimirovna Khutornaya; Anastasia Valerievna Ponasenko; E V Grigoriev (Байкальский медицинский журнал)
Introduction: It is known that the variability of immune response genes and the corresponding immune profile modulate the risk of a number of pathologies. Understanding the role of the immunogenetic status based on the variability of innate immunity receptors in the dynamics of the systemic inflammatory response of non-infectious genesis in open cardiac surgery, as well as the issues of objective assessment and possible correction of complications in the form of multiple organ failure (MOF), remain relevant.Objective: To determine those alleles of the TREM1 gene that are associated with the risk of developing POF in patients after coronary artery bypass grafting and which levels of sTREM1 may be of diagnostic significance.Materials and methods: A comprehensive examination of 680 patients with atherosclerosis of the coronary arteries was performed on the basis of the Federal State Budgetary Scientific Institution "NII KPSSZ" in the preoperative and early postoperative periods of coronary artery bypass grafting. Two groups were retrospectively formed, differing in the presence/absence of MOF in the early postoperative period. Based on clinical and laboratory data, the first group included 30 patients (4.4%) with MOF established in the early postoperative period (SOFA score over 4 points, combined dysfunction of 2 or more systems with further progression of organ disorders) and 650 patients (95.6%) were included in the second group - with an uncomplicated course of the postoperative period (score on the SOFA scale less than 4 points, disorders of 1-2 organ systems that occur with minor clinical manifestations and do not require long-term correction and support). Serum concentrations were determined by ELISA twice - before surgery and 24 hours (1 day) after surgery. Genotyping of 8 TREM1 polymorphic variants (rs1817537, rs3804277, rs6910730, rs7768162, rs2234246, rs4711668, rs9471535, rs2234237) was performed according to the protocol of the TagMan probe manufacturer by PCR with real-time detection of amplification products. Statistical data processing was carried out using SNPstats and GraphPad Prism 8 software.Results: It was found that in individuals with the T rs2234246 allele (p=0.0076), the G rs1817537 allele (p=0.019) and the T rs3804277 allele (p=0.019) of TREM1, the risk of developing POF after coronary artery bypass grafting increases. Carrying a homozygous genotype for a rare allele in these polymorphic variants is associated with a high concentration of sTREM1 at the preoperative stage (p=0.0005). It was also found that the most pronounced increase in the concentration of sTREM1 in the preoperative and early postoperative periods was observed in critically ill patients. Differences in sTREM1 concentrations between groups were significant throughout the intraoperative period (p<0.0001 and p<0.0001, respectively).Conclusion: It has been established that the concentration of sTREM and the carriage of rare alleles in certain polymorphic sites of the TREM1 gene (T rs2234246 allele, G rs1817537 allele and T rs3804277 allele), as well as their relationship with the level of circulating sTREM, demonstrate their significance in the development of MOF in patients with coronary artery disease after undergoing coronary artery bypass grafting.